Pengaruh Kualitas Pelayanan, Fasilitas dan Harga Terhadap Kepuasan Konsumen di Hotel Bintang Empat - Muhammad Falaq (Politeknik Harapan Bersama, 2023)
Many factors can influence hotel customer satisfaction, including good service quality, adequate facilities, and reasonable prices. The hotel will serve as a stopover for customers, so those who come to visit will think about these three factors that will affect their satisfaction. As a result, the goal of this research was to determine the impact of service quality, facilities, and pricing at the Swiss-Belinn Bogor hotel. This study employed a descriptive method with a quantitative approach. The participants in this study were all guests at the Swiss-Belinn Bogor hotel. The sample in this study was determined by applying the Slovin formula, which yielded 100 respondents using a simple random sampling technique. The Multiple Linear Regression Analysis Test was used in this study, along with tools to process data from the IBM SPSS Statistics 26 application. The Multiple Linear Regression Analysis Test demonstrates that service quality, facilities, and pricing all have a positive impact on customer satisfaction